PROCESS WRITING: SUCCESSFUL AND UNSUCCESSFUL WRITERS; DISCOVERING WRITING BEHAVIOURS - Baroudy, Ismail (International Journal of English Studies, 2008)
Successful and unsuccessful strategies practically complied with in the act of writing have been so far experimentally tapped and scholastically rehearsed by several authors. In this study, a complementary task using a questionnaire worked out to comprehensively specify and cover almost all types of writing behaviours has been inquisitively manipulated. By analysing and inspecting the findings elicited from student-writers’ response sheets, successful and unsuccessful writing strategies are then contrastively identified, categorised and demonstrated. Based on the awareness accomplished, writing teachers’ consciousness will be raised and boosted, thus, helping their poor student-writers justifiably quit their debilitative habits and adopt instead, facilitative ones, those competent writers implement while writing. In the questionnaire, the student-writers would reflect upon their creeping experience and pass informative judgements about their own strategies. Student-writers will respond to fact-finding statements regarding five writing components delineated as rehearsing, drafting, revising, student-writers’ role and the role of instructional materials